Source of Funds and Islamic Insurance Growth: Investment Returns as a Mediation - Dhidhin Noer Ady Rahmanto; Muhammad Iqbal Fasa; Khoirul Rijal (al-Uqud : Journal of Islamic Economics, 2020)
Sustainable growth must be maintained by maintaining an increase in investment returns, with the source of funds as a stimulant. The population of this study was all Islamic life insurance companies in Indonesia. The study used path analysis mediation with regression or two layers OLS (Ordinary Least Squares) and followed by Sobel test. The result showed that investment returns can mediate participant funds in influencing the growth of Islamic life insurance companies. Meanwhile, investment returns did not mediate the influence of company funds in influencing the growth of Islamic life insurance companies.